Tìm x:
(3,6+x):x-0,8=1,4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b)
x – 5,7 = 7,25
x = 7,25 + 5,7
x = 12,95
x x 1,4 = 5,6
x = 5,6 : 1,4
x = 4.
x + 14,28 = 12,5 x 3,6
x + 14,28 = 45
x = 45 – 14,28
x = 30,72
x : 2,75 = 37,6 – 18,62
x : 2,75 = 18,98
x = 18,98 x 2,75
x = 52,195.
-0.6x-4.5x-1+4x+0.8=3.6
x(-0.6-4.5+4)+(-1+0.8)=3.6
-0.1x-0.2 =3.6
-0.1x =3.6+0.2
-0.1x =3.8
x =3.8/(-0.1)
x =-38
a) x + x : 4 *1,6 + x : 6*3,6 = 222
\(\Rightarrow x+x\cdot0,4+x.0,6=222\)
\(\Rightarrow x.\left(1+0,4+0,6\right)=222\)
\(\Rightarrow x.2=222\)
\(\Rightarrow x=222:2=111\)
b) \(\left(x+0,2\right)+\left(x+0,4\right)+...+\left(x+1\right)=9,6\)
\(\Rightarrow\left(x+x+x+x+x\right)+\left(0,2+0,4+0,6+0,8+1\right)\) =9,6
\(\Rightarrow5.x+\left[\left(1-0,2\right):0,2+1\right].\left(1+0,2\right):2\) = 9,6
\(\Rightarrow5.x+3=9,6\)
\(\Rightarrow5.x=9,6-3=6,6\)
\(\Rightarrow x=6,6:5=1,32\)
(x+0,2)+(x+0,4)+(0,6)+(0,8)+(x+1)=9,6
5x+(0,2+0,4+0,6+0,8+1)=9,6
5x+3=9,6
5x =9,6-3
5x =6,6
x =6,6:5
x =1,32
a) \(\left(\frac{2}{5}x-2\right)-\left(\frac{3}{2}x+1\right)-\left(-4x-\frac{4}{5}\right)=\)\(\frac{18}{5}\)
\(\frac{2}{5}x-2-\frac{3}{2}x-1-4x+\frac{4}{5}=\frac{18}{5}\)
\(\frac{2}{5}x-\frac{3}{2}x-4x=\frac{18}{5}+2+1-\frac{4}{5}\)
\(\frac{8}{20}x-\frac{30}{20}x-\frac{80}{20}x=\frac{14}{5}+3\)
\(\frac{-51}{10}x=\frac{14}{5}+\frac{15}{5}\)
\(\frac{-51}{10}x=\frac{29}{5}\)
\(x=\frac{29}{5}.\frac{-10}{51}\)
\(x=\frac{-58}{51}\)
vậy \(x=\frac{-58}{51}\)
\(\left|x-3,6\right|=1,4\\ \Rightarrow\left[{}\begin{matrix}x-3,6=1,4\\x-3,6=-1,4\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=5\\x=2,2\end{matrix}\right.\)
\(\left|x-3,6\right|=1,4\)
\(\Leftrightarrow\orbr{\begin{cases}x-3,6=1,4\\x-3,6=-1,4\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=5\\x=2,2\end{cases}}\)
Vậy ...
\(\left(0,4x-2\right)-\left(1,5x+1\right)\) \(\left(-4x-0,8\right)\)\(=3,6\)
<=>\(\left(0,4x-2\right)-\)\(\left(-6x^2-1,2x-4x-0,8\right)\)\(=3,6\)
<=> \(0,4x-2+6x^2+1,2x\)\(+4x+0,8=3,6\)
<=> \(6x^2+5,6x-1,2=3,6\)
<=> \(6x^2+5,6x-4,8=0\)
<=>
0.8 x 46.5 x 9 + 0.72 x 530 + 3.6
= 0.72 x 46.5 + 0.72 x 530 + 5 x 0.72
= 0.72 x ( 46.5 + 530 + 5 )
= 0.72 x 401.5
= 298.08